Investigating Crimes against Public Morality and Decency in Cyberspace from The Perspective of Criminology - Saeed Mardani; Mahmoud Bavi; Seyyed Bassem Mavallyzadeh (Jurnal Cita Hukum, 2022)
Criminalizing violations of public morals and morals on the internet will help lawmakers understand the strengths and weaknesses of the criminal problem. The act of the perpetrator violates the basic principle of freedom, and is a heinous act, and extreme means must be used to prevent and limit the perpetrator of the crime. Perpetrators commit crimes by trapping their victims using crime equipment such as computers, cell phones, and the internet. This study uses a qualitative research method with an empirical approach. The results of the study state that cybercrimes involve perpetrators who gain material benefits from violations through social media platforms such as Facebook, Instagram, and Telegram. Violation of perpetrators related to cyberspace can be overcome by implementing integrated countermeasures based on situational tactics, development, and social control. In addition to providing the necessary education and information.Keywords: Ethics; Chastity; Cyberspace; CriminologyPenyelidikan Kejahatan Terhadap Kesusilaan Dan Kesusilaan Umum Di Dunia Maya Dari Perspektif Kriminologi AbstrakMengkriminalisasikan pelanggaran moral dan kesusilaan publik di internet akan membantu pembuat undang-undang memahami kekuatan dan kekurangan masalah tindak kriminal. Tindakan pelaku melanggar prinsip dasar kebebasan, dan merupakan tindakan keji, dan harus digunakan cara ekstrem untuk mencegah dan membatasi pelaku tindak kejahatan. Pelaku melakukan kejahatan dengan cara menjebak korbannya dengan menggunakan peralatan kejahatan seperti komputer, ponsel, dan internet. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan empiris. Hasil penelitian menyatakan bahwa kejahatan dunia maya melibatkan pelaku yang memperoleh keuntungan materi dari pelanggaran melalui platform media sosial seperti Facebook, Instagram, dan Telegram. Penyimpangan pelaku terkait dunia maya dapat diatasi dengan menerapkan tindakan pencegahan terpadu berdasarkan taktik situasional, pengembangan, dan kontrol sosial. Selain memberikan pendidikan dan informasi yang diperlukan.Kata Kunci: Etika; Kesucian; Dunia Maya; Kriminologi Расследование преступлений против общественной морали и нравственности в киберпространстве с точки зрения криминологии АннотацияКриминализация нарушений общественной морали и нравственности в Интернете поможет законодателям понять сильные и слабые стороны криминальной проблемы. Действие преступника нарушает основной принцип свободы и является гнусным деянием, и необходимо использовать крайние средства, чтобы предотвратить и ограничить виновного в совершении преступления. Преступники совершают преступления, заманивая своих жертв в ловушку с помощью криминального оборудования, такого как компьютеры, мобильные телефоны и Интернет. В данном исследовании используется качественный метод исследования с эмпирическим подходом. Результаты исследования показывают, что в киберпреступлениях участвуют преступники, которые получают материальную выгоду от нарушений через социальные сети, такие как Facebook, Instagram и Telegram. Нарушения правонарушителей, связанные с киберпространством, можно преодолеть путем реализации комплексных мер противодействия, основанных на ситуационной тактике, развитии и социальном контроле, а также предоставления необходимого образования и информации.Ключевые слова: Этика; Целомудрие; Киберпространство; Криминология